Physics Matters - Natarajan, Vasant (New Jersey: World Scientific, 2017)
"This is a collection of essays on physics topics. It is written as a textbook for non-physics science and arts students, at the undergraduate level. Topics covered include cellphone radiation, lasers, the twin paradox, and more"--
Oscillations -- The myth of cell phone radiation -- What Einstein meant when he said "God does not play dice ..." -- Einstein as armchair detective--the case of stimulated radiation -- Standard for units -- The twin paradox in relativity -- Robert Dicke and atomic physics -- The 1997 Nobel Prize in physics--Laser cooling and trapping -- The 2001 Nobel Prize in physics--Bose-Einstein condensation -- The 2005 Nobel Prize in physics--Laser physics -- The 2009 Nobel Prize in physics--Achievements in that have changed modern life -- The 2012 Nobel Prize in physics--Manipulation of single particles.
Includes index.
Keywords: Physics